Effectiveness of Group Poetry Therapy of Mazza’s Multidimensional Model (Based on the Romantic Debates of Ferdowsi’s Shahnameh) on Response to Intrusion Memories, Automatic Thoughts and Affect Balance in Female Students with Premenstrual Dysphoric Disorde - Senobar Limakeshi, Laleh; Sharifi Fard, Sayed Ali; Bagher Pour, Arefeh (Psychology of Woman Journal, 2023)
Objective: Iranian culture has always been mixed with Persian poetry and literature. Poetry therapy is also considered one of the complementary methods of psychotherapy. The present study aims to investigate the effectiveness of group poetry therapy of Mazza’s multidimensional model (based on Shahnameh Ferdowsi’s romantic debates) on Response to Intrusions, automatic thoughts, and affect balance in female students with premenstrual dysphoric disorder. Method: The research method was quasi-experimental. The statistical population included all students living in the dormitory of Farhangian University of Ardabil, and from this population, during three stages, 20 participants with premenstrual dysphoric disorder were selected as samples in two experimental and control groups. Measures including the Response to Intrusions Questionnaire, Automatic Thoughts Questionnaire, and Affect Balance Scale were performed on both groups, and the poetry therapy protocol based on Shahnameh Ferdowsi’s romantic debates was performed on the experimental group. Results: The findings showed that after controlling the effects of the pre-test, the experimental group had a significant improvement in each of the factors of negative interpretation (F= 40.990, p<0.01), rumination (F=23.367, p<0.01), suppression (F=13.753, p<0.01), distress (F=16.924, p<0.01), automatic thoughts (F=28.874, p<0.01), positive affect balance (F=13.892, p<0.01) and negative affect balance (F=55.887, p<0.01). Conclusion: Based on findings, Ferdowsi’s romantic debates in the context of group therapy can lead to a reduction of PMDD symptoms by launching positive therapeutic components such as catharsis and empathy.